Authigenic 10Be/9Be ratios and 10Be-fluxes (230Thxs-normalized) in central Baffin Bay sediments during the last glacial cycle: Paleoenvironmental implications. (15th May 2016) - Simon, Quentin; Thouveny, Nicolas; Bourlès, Didier L.; Nuttin, Laurence; Hillaire-Marcel, Claude; St-Onge, Guillaume
Abstract: Authigenic 10 Be/ 9 Be ratios and 10 Be-fluxes reconstructed using the 230 Thxs normalization, proxies of the cosmogenic radionuclide 10 Be production rate in the atmosphere, have been measured in a sedimentary core from Baffin Bay (North Atlantic) spanning the last 136 ka BP. The normalization applied on the exchangeable (authigenic) 10 Be concentrations using the authigenic 9 Be isotope and 230 Thxs methods yield equivalent results strongly correlated with sedimentological parameters (grain-size and mineralogy). Lower authigenic beryllium (Be) concentrations and 10 Be/ 9 Be ratios are associated with coarse-grained carbonate-rich layers, while higher authigenic Be values are related to fine-grained felspar-rich sediments. This variability is due to: i) sediment composition control over beryllium-scavenging efficiency and, ii) glacial history that contributed to modify the 10 Be concentration in Baffin Bay by input and boundary scavenging condition changes. Most paleo-denudation rates inferred from the 10 Be/ 9 Be ratio vary weakly around 220 ± 76 tons.km −2 .yr −1 (0.09 ± 0.03 mm.yr −1 ) corresponding to relatively steady weathering fluxes over the last glacial cycle except for six brief intervals characterized by sharp increases of the denudation rate. These intervals are related to ice-surging episodes coeval with Heinrich events and the last deglaciation period. An average freshwater flux of 180.6 km 3 .yr −1 (0.006 Sv), consistent with recent models, has been calculated in order to sustain glacially-derived 10 Be inputs into Baffin Bay. It is concluded that in such environments, the authigenic 10 Be measured mainly depends on climatic effects related to the glacial dynamics, which masks the 10 Be production variation modulated by geomagnetic field changes. Altogether, these results challenge the simple interpretation of 10 Be-concentration variation as a proxy of Interglacial/Glacial (interstadial/stadial) cycles in Arctic and sub-Arctic regions. They rather suggest the effect of higher-frequency paleoclimatic changes and local glacial dynamics on 10 Be signature. Highlights: 10 Be/ 9 Be ratios and 10 Be-fluxes yield equivalent results from glaciomarine sediments. 10 Be-systematic variability mainly obeys to glacio-climatic condition changes. 10 Be production proxies do not allow to characterize the geomagnetic features in PC16. Denudation rates are steady except for brief ice surging episodes coeval to H-events. 10 Be concentration is controlled by freshwater inputs from regional Ice Sheets.